Technical report: prediction of population in Malaysia by using numerical methods / Anis Syazriena Abdul Manaf, Nur Najihah Md Ali and Nurul Asyiqin Mohd Husin - Abdul Manaf, Anis Syazriena; Md Ali, Nur Najihah; Mohd Husin, Nurul Asyiqin (2016)
This project is conducted for finding the best numerical method on calculating population in Malaysia. Starting from year 2011 until 2014, the method used is Euler's Method and Runge-Kutta Method. Before implementing both methods, the formulas have to derive in terms of population. The accuracy and minimum errors obtained for both methods, Since Euler's Method and Runge-Kutta Method is classified under numerical ordinary differential equation, the decision was made on differential equation for pursuing the calculation. Population data is collected which is secondary data from the website. Next, the project continued with decision on method. Forward Euler's Method and Runge-Kutta method was chosen and necessary for the data. The data collected was divided into population for both genders, population for males and females with it's population growth rate, k. The population growth rate, k is classified for three parts computation, which are constant value k, average value k and different value of k. All the calculation is generated by Maple Software including error analysis as a result for this project. As the result, Euler's Method is the best method as compared to the Runge-Kutta method since the precision of the data is closer to the actual data. The derivation of the Euler's Method Formula and Runge-Kuna formula, the prediction of the population using Euler's Method and Runge-Kutta Method and to determine the best method on predicting the population in Malaysia by calculating the error for both method is achieved.